Simulación numérica de problemas con no linealidad física y geométrica. Análisis de consolidación de suelos no saturados - Di Rado, Héctor Ariel (2006)
The main goal of the present work is to develop a mathematical model, and the corresponding finite element program, for the description of the physical and geometrical non linear mechanical behavior of non saturated soft compressible clay-type soils commonly found in the North East Region of Argentina. For the soil consolidation mathematical model, an approach based on the geological mass stress state combination is developed. Concerning with the non linear simulation, in the first place a hypoelastic description based on co rotated stress for any elastoplastic solid is carried out. Afterwards, this description is extended to non saturated porous materials. To obtain the discrete or algebraic form of the precedent equations, the Finite Element Method is applied. Many different examples, including structural analysis problems, for which previous solutions are known, were solved and through encouraging results it can be stated that for both separated and assembled mathematical models, the practical cases are adequately simulated and therefore, the hypotheses were verified.